(NkWANTOWAQ MEHANIKA S ZADA^AMI (B:s (Nu^EBNOE POSOBIE (B/s - (NeL@TIN(B, (Np(B.(Nw(B. s; (NbOGOL@BOW(B, (Nn(B.(Nn(B.s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1976)
(NpREDM(B. (NUKAZ(B.: (NS(B. 332 - 333s
(NsPISOK LIT(B. (NS(B. 328 - 331s
Keywords: (NkWANTOWAQ TEORIQs